Primary myoblasts from intrauterine growth-restricted fetal sheep exhibit intrinsic dysfunction of proliferation and differentiation that coincides with enrichment of inflammatory cytokine signaling pathways. (1st August 2022) - Posont, Robert J; Most, Micah S; Cadaret, Caitlin N; Marks-Nelson, Eileen S; Beede, Kristin A; Limesand, Sean W; Schmidt, Ty B; Petersen, Jessica L; Yates, Dustin T
Abstract: Intrauterine growth restriction (IUGR ) is linked to lifelong reductions in muscle mass due to intrinsic functional deficits in myoblasts, but the mechanisms underlying these deficits are not known. Our objective was to determine if the deficits were associated with changes in inflammatory and adrenergic regulation of IUGR myoblasts, as was previously observed in IUGR muscle. Primary myoblasts were isolated from IUGR fetal sheep produced by hyperthermia-induced placental insufficiency (PI-IUGR ; n = 9) and their controls ( n = 9) and from IUGR fetal sheep produced by maternofetal inflammation (MI-IUGR ; n = 6) and their controls ( n = 7). Proliferation rates were less ( P < 0.05) for PI-IUGR myoblasts than their controls and were not affected by incubation with IL-6, TNF-α, norepinephrine, or insulin. IκB kinase inhibition reduced ( P < 0.05) proliferation of control myoblasts modestly in basal media but substantially in TNF-α-added media and reduced ( P < 0.05) PI-IUGR myoblast proliferation substantially in basal and TNF-α-added media. Proliferation was greater ( P < 0.05) for MI-IUGR myoblasts than their controls and was not affected by incubation with TNF-α. Insulin increased ( P < 0.05) proliferation in both MI-IUGR and control myoblasts. After 72-h differentiation, fewer ( P < 0.05) PI-IUGR myoblasts were myogenin + than controls in basal and IL-6 added media but not TNF-α-added media. Fewer ( P < 0.05) PI-IUGR myoblasts were desmin + than controls in basal media only. Incubation with norepinephrine did not affect myogenin + or desmin + percentages, but insulin increased ( P < 0.05) both markers in control and PI-IUGR myoblasts. After 96-h differentiation, fewer ( P < 0.05) MI-IUGR myoblasts were myogenin + and desmin + than controls regardless of media, although TNF-α reduced ( P < 0.05) desmin + myoblasts for both groups. Differentiated PI-IUGR myoblasts had greater ( P < 0.05) TNFR1, ULK2, and TNF-α-stimulated TLR4 gene expression, and PI-IUGR semitendinosus muscle had greater ( P < 0.05) TNFR1 and IL6 gene expression, greater ( P < 0.05) c-Fos protein, and less ( P < 0.05) IκBα protein. Differentiated MI-IUGR myoblasts had greater ( P < 0.05) TNFR1 and IL6R gene expression, tended to have greater ( P = 0.07) ULK2 gene expression, and had greater ( P < 0.05) β-catenin protein and TNF-α-stimulated phosphorylation of NFκB. We conclude that these enriched components of TNF-α/TNFR1/NFκB and other inflammatory pathways in IUGR myoblasts contribute to their dysfunction and help explain impaired muscle growth in the IUGR fetus. Lay Summary: Myoblasts are stems cells whose functional capacity can limit muscle growth. However, stressful intrauterine conditions cause these cells to be intrinsically dysfunctional. This restricts muscle growth capacity, leading to intrauterine growth restriction (IUGR ) of the fetus, low birth weight, and less muscle mass after birth. Consequently, meat yield is reduced in IUGR-born food animals and glucose homeostasis is impaired in IUGR-born humans, which contributes to metabolic dysfunction. Intrinsic dysfunction of IUGR myoblasts has been previously observed, but the fetal programming changes (i.e., permanent changes in the development of cellular mechanisms that explains different functional outcomes) have not been identified. This study shows that one mechanism is the enhancement of signaling pathways for TNF-α and other inflammatory cytokines. These cytokines have roles in stress responses and regulation of muscle growth. Programmed enhancement of these pathways means that IUGR myoblasts are more responsive to even normal amounts of circulating cytokines. Unfortunately, the primary response of myoblasts to cytokines is slower differentiation (i.e., cellular transformation necessary for muscle growth). Programmed enhancement of this response directly impedes myoblast-dependent muscle growth, and the deficit is lifelong. However, identifying this mechanism is a fundamental step for developing strategies to improve muscle growth in low birth weight offspring. Abstract : Mechanisms underlying the link between low birth weight and poor muscle growth must be identified in order to improve outcomes and recover value in low birth weight livestock. This study shows that one mechanism is the enhancement of inflammatory regulation of the stem cells responsible for muscle growth.